Research on driver injuries in vehicle rear-end collisions considering different overlap rate and speed difference - Hanyu Liu; Daowen Zhang; Yihong Zhang (Scientific Reports)
Abstract Rear-end collisions involving passenger vehicles often result in significant injuries and fatalities, with the driver of the trailing vehicle being particularly vulnerable to severe harm. This study analyzes regulations related to rear-end collisions and their necessity, and develops finite element models of the vehicle, dummy, and airbags. The positioning of the dummy is based on C-NCAP standards, and the Primer software is utilized to model and integrate the seatbelt and airbags. Subsequently, the model is solved using LS-DYNA. Additionally, the study examines the effects of varying overlap rates and speed differences on the injuries sustained by the driver of the trailing vehicle. The research reveals that both overlap rate and speed difference have a significant impact on the extent of injury to the driver in rear-end collisions. Notably, in scenarios with low overlap and high speed differences, the driver experiences more severe injuries, particularly to the head, neck, and lumbar spine. Furthermore, the study demonstrates that, for the same speed, when the overlap rate exceeds 30%, the severity of the injuries to the driver increases as the overlap rate rises. In particular, at a 40% overlap rate, injuries to the neck, chest, and lumbar spine are most severe. Based on the simulation results, this paper validates the rationality of the current Chinese regulations concerning crash scenarios and proposes recommendations for revisions to improve traffic safety and reduce injury in rear-end collisions.